Tendencies of financing investment projects in Kazakhstan - Nurseitov A.A., Isabekova M.A. (Journal of Economic Research & Business Administration, 2016)
This article examines trends in the financing of public and non-public investment projects in Kazakhstan based on the analysis of the data on the expertise of investment projects carried out by the Kazakhstan public-private partnership center. Selection of one of the five ways of financing investment projects envisaged by the legislation of Kazakhstan depends on the reasonability and effectiveness (economic, social, commercial) of the particular project. The analysis showed that traditional ways of financing projects from the state budget have become less popular. At the same time, the number of examined projects involving private investments with the fulfillment of public obligations or borrowing from non-governmental entities on the condition of a state guarantee is gradually increasing. These trends are reflection of the changes that occur in the economic situation of Kazakhstan.